Machine and sovereignty : for a planetary thinking - Hui, Yuk, 1985- (Minneapolis, MN : University of Minnesota Press, 2024)
"Machine and Sovereignty offers a future-oriented mode of political thought that encompasses the unprecedented global challenges we are confronting: the rise of artificial intelligence, the ecological crisis, and intensifying geopolitical conflicts. Arguing that a new approach to planetary thinking is urgently needed, Yuk Hui presents new epistemological and technological frameworks for understanding and rising to the crises of our present and our future"-- "Machine and Sovereignty offers a future-oriented mode of political thought that encompasses the unprecedented global challenges we are confronting: the rise of artificial intelligence, the ecological crisis, and intensifying geopolitical conflicts. Arguing that a new approach to planetary thinking is urgently needed, Yuk Hui presents new epistemological and technological frameworks for understanding and rising to the crises of our present and our future"--